Elective Repeated Cesarean Section (ERCS) - Azal Sadiq (Academic International Journal of Medical Sciences, 2023)
Objective: To investigate the timing of elective repeat cesarean deliveries at Al-Batool Teaching Hospital in Diyala, Iraq. Methods: A retrospective analysis was conducted of 100 women who underwent elective repeat cesarean delivery at 37-40 weeks gestation at Al-Batool Teaching Hospital. Emergency cesarean deliveries were excluded. Results: The majority of elective repeat cesarean deliveries (78%) were performed at 37 weeks gestation. Cesarean deliveries at 38, 39, and 40 weeks accounted for 4%, 2%, and 16% of the sample, respectively. Conclusions: In this cohort, most elective repeat cesarean deliveries were conducted at 37 weeks gestation, rather than the recommended 40 weeks. Delivering earlier than 39-40 weeks in the absence of medical indications reduces the chances of successful vaginal birth after cesarean. These findings suggest that evidence-based protocols were not consistently followed for timing of elective repeat cesarean sections at this institution. Further research is needed to identify barriers to adhering to delivery guidelines and implement quality improvement initiatives to optimize cesarean delivery timing when clinically appropriate.